Upaya Meningkatkan Hasil Belajar Kognitif Geografi Siswa Kelas X pada Materi Litosfer Melalui Penerapan Soal Evaluasi Bentuk Uraian di SMAN 61 Jakarta - Sarah Ummu Azizah; Ode Sofyan Hardi; Lia Kusumawati (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the improvement of students' cognitive learning outcomes in geography through the application of essay evaluation questions on lithosphere materials. Data collection was carried out from January-February 2023, at SMAN 61 Jakarta. The research method used by the researcher is a quantitative method with true experimental approach, and pretest-posttest control group design, where the researcher acts as a teacher in class, assisted by subject teachers as collaborators. The instrument used is a formative test on lithosphere material in the form of essay questions consisting of 8 questions. The results show that the application of evaluation questions through essay form in improving students' cognitive learning outcomes in geography has a varied range of measurable cognitive level results, from C1 to C6. Students have freedom to express their thoughts and explore in choosing answers, which allows for a broader and more complex measurement of cognitive thinking abilities.